Malocclusion traits as risk indicators for depression in young adults: A population-based cross-sectional study - Ahmed A. Alsulaiman (Saudi Dental Journal)
Background: Although malocclusion has historically drawn attention for its effects on craniofacial development, oral function, and aesthetics, recent studies have started to investigate the possible association between malocclusion and other aspects of overall health, such as mental health. Objectives: This study aimed to analyze various dental malocclusion characteristics and their potential association with depressive symptoms among young adults. The National Health and Nutrition Examination Survey was used for data procurement. Methods: This cross-sectional study was conducted using a nationally representative population sample, including data from 3,806 participants surveyed between 1988 and 1994 under the National Health and Nutrition Examination Survey III. The inclusion criteria were completion of the clinical assessment for malocclusion traits, being dentate, reporting no history of previous or current orthodontic treatment, reporting no dental pain, and responding to a questionnaire about psychiatric status. Statistical evaluations involved logistic regression modeling and chi-squared tests, considering the complex sampling design nature of the survey. Results: Crude and adjusted logistic regression models indicated no significant association between malocclusion traits and major depressive episodes (MDEs). Conversely, the same models revealed a positive association between malocclusion traits (specifically, upper crowding and two or more cumulative malocclusion traits) and dysthymia in both crude and adjusted analyses. Conclusion: Specific malocclusion traits were associated with dysthymia, whereas no such associations existed with MDEs. These findings suggest that the association between malocclusion and depression is complex and multifaceted.